Climate variability, climate change,and fisheries - Glantz, Michael H. (Cambridge University, 2013)
This volume, Climate Variability, Climate Change, and Fisheries,addresses the potential implications for fisheries and societies of the regional impacts of a global warming of the atmosphere. Fisheries case studies were selected for investigation of the responses to changes in their environment.